Habitat segregation of plate phenotypes in a rapidly expanding population of three‐spined stickleback. Issue 6 (9th June 2021) - Eriksson, Britas Klemens; Yanos, Casey; Bourlat, Sarah J.; Donadi, Serena; Fontaine, Michael C.; Hansen, Joakim P.; Jakubavičiūtė, Eglė; Kiragosyan, Karine; Maan, Martine E.; Merilä, Juha; Austin, Åsa N.; Olsson, Jens; et al.
Abstract: Declines of large predatory fish due to overexploitation are restructuring food webs across the globe. It is now becoming evident that restoring these altered food webs requires addressing not only ecological processes, but evolutionary ones as well, because human‐induced rapid evolution may in turn affect ecological dynamics. We studied the potential for niche differentiation between different plate armor phenotypes in a rapidly expanding population of a small prey fish, the three‐spined stickleback ( Gasterosteus aculeatus ). In the central Baltic Sea, three‐spined stickleback abundance has increased dramatically during the past decades. The increase in this typical mesopredator has restructured near‐shore food webs, increased filamentous algal blooms, and threatens coastal biodiversity. Time‐series data covering 22 years show that the increase coincides with a decline in the number of juvenile perch ( Perca fluviatilis ), the most abundant predator of stickleback along the coast. We investigated the distribution of different stickleback plate armor phenotypes depending on latitude, environmental conditions, predator and prey abundances, nutrients, and benthic production; and described the stomach content of the stickleback phenotypes using metabarcoding. We found two distinct lateral armor plate phenotypes of stickleback, incompletely and completely plated. The proportion of incompletely plated individuals increased with increasing benthic production and decreasing abundances of adult perch. Metabarcoding showed that the stomach content of the completely plated individuals more often contained invertebrate herbivores (amphipods) than the incompletely plated ones. Since armor plates are defense structures favored by natural selection in the presence of fish predators, the phenotype distribution suggests that a novel low‐predation regime favors stickleback with less armor. Our results suggest that morphological differentiation of the three‐spined stickleback has the potential to affect food web dynamics and influence the persistence and resilience of the stickleback take‐over in the Baltic Sea.